Self-regulated learning skills in vocational students based on their self-evaluation - Meidi Sirk (International Journal for Research in Vocational Education and Training (IJRVET), 2025)
Context: The importance of both self-regulated and self-directed learners has been emphasised in lifelong learning. However, in theory, self-regulated learning (SRL) serves as a basis for becoming a self-directed learner. Therefore, SRL (which includes certain skills) needs to be developed in vocational education and training alongside specialist training in order to meet the demands of the labour market, where employees should be capable of continuous learning. Previous studies based on the experiences of vocational teachers, and mainly focusing on adolescent students, have highlighted that many vocational students have low levels of SRL skills. However, there is a lack of research exploring student perspectives on their own SRL skills. It is unclear what factors influence their SRL and what support they need for developing SRL. The aim of this article is to analyse and describe the differences in the SRL skills of vocational students based on their self-evaluation and the factors related to their SRL. Methods: The author conducted diverse quantitative analyses of the responses of 244 students to achieve the research aim. First, a factor analysis was performed on the five skill areas of SRL, followed by a K-means cluster analysis based on SRL skills factors. Then SRL clusters of students were analysed according to the students' socio-demographic factors, learning difficulties, and other learning factors using cross-tabulation and variance analysis. Findings: From an SRL perspective, the most important factors in distinguishing and characterising the clusters of students were the skills related to plan management and organisation. On this basis, the study identified three clusters, consisting of students with: 1) Difficulties in organisation and behaviour (30%), 2) difficulties in planning and time management (20%), and 3) good and balanced SRL skills (50%). Conclusion: Overall, the study found that half of the students exhibited good SRL skills and these students encountered fewer learning difficulties. They also studied more through collaborative learning activities, received sufficient verbal feedback, and showed higher levels of motivation towards their schoolwork. However, the remaining students require additional support to improve their SRL skills.
Keywords: 330; Vocational Education and Training; VET; Vocational Students; Self-Regulation; Self-Regulated Learning Skills